2013
DOI: 10.4034/pboci.2013.132.01
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de Neoplasias, Cárie e Gengivite em Pacientes Oncológicos Pediátricos no Município de Belém, Pará

Abstract: Objetivo: Avaliar clinicamente a prevalência de cárie e gengivite em 62 crianças de 3 a 12 anos de idade, de ambos os gêneros sendo que 32 eram portadoras de neoplasias e 30 eram saudáveis, fazendo parte do grupo controle. Métodos: Os pacientes foram avaliados utilizando-se os índices CPO-d, ceo-d, Índice de Placa (IP) e Índice gengival (IG), sendo avaliados em dois momentos, antes e seis meses após o início do estudo. Na análise estatística, para verificar a interdependência entre as variáveis, utilizaram-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
3
6
0
6
Order By: Relevance
“…The data also are consistent with the prevalence observed in research conducted in Belém do Pará [10], where found a percentage of 59.37% for male and 40.63% for female. The incidence of studies in Brazil confirms that the highest prevalence of childhood cancer affects males in most tumors [10].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The data also are consistent with the prevalence observed in research conducted in Belém do Pará [10], where found a percentage of 59.37% for male and 40.63% for female. The incidence of studies in Brazil confirms that the highest prevalence of childhood cancer affects males in most tumors [10].…”
Section: Discussionsupporting
confidence: 81%
“…The incidence of studies in Brazil confirms that the highest prevalence of childhood cancer affects males in most tumors [10].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Slightly more than half of the patients were diagnosed with ALL, and most of them underwent chemotherapy as treatment. The same result was observed in the studies by Lopes et al [7], Santos et al [6] and Figueiredo & Nogueira [11]. Oral health is critical for health, since it is through the mouth that individual feeds, thus obtaining the nutrients necessary to be alive and healthy, as well as other functions.…”
Section: Discussionsupporting
confidence: 79%
“…Ainda sobre o CPO-D, o componente cariado foi o mais expressivo (média de 2,7) em relação aos componentes perdidos e obturados (média de 0,4 e 2,1 respectivamente), outro estudo também verificou que em crianças portadoras de câncer e saudáveis o CPO-D apresentou maior número de dentes cariados 13 .…”
Section: Discussionunclassified